(untitled) (Third Sector Social Economic Review, 2023)
When the literature on the role of cooperatives in social and economic life is examined; apart from the public and private sectors, it is seen that as the third sector, it has an economic share above its social awareness. Contrary to the limited size of the public in the economy, the failure of the market, and the private sector, which acts with the goal of profit maximization, cooperatives are entrepreneurial institutional organizations with different types on the basis of solidarity economy. Turkey could not reach the desired level in practice on the basis of the desired mobilization simultaneously with the developed social economies in the strong cooperative understanding. In addition to legislative regulations and the work of public authorities, it seems that more participant support is needed to solve the structural problems encountered in practice. Contrary to the structure expected from the principles and values of strong cooperatives, the problems behind the fragile structure are investigated by experts and academics from different circles. In our study, the structuring model for this sector, which has priority in meeting social needs most effectively in today’s, future and crisis periods, was analyzed. The role of participating stakeholders was also evaluated and the reasons for restructuring for cooperatives were examined from manager experiences. The research was carried out with experts who have worked as cooperative managers and supervisors for 20 years or more in the provinces and districts of the Aegean Region. In this qualitative study, the findings obtained by the thematic analysis method were interpreted with visual expression. In the result evaluation reached; suggestions that will serve to bring together legislation, education, institutional structure, formation of new institutions, control mechanisms, financial empowerment solutions, partnership awareness, and the values of cooperatives are explained.